Knowledge of Brazilian Dentists about Dentoalveolar Trauma Care and their Experiences during the COVID-19 Pandemic - Lívia Pessamílio Soares; Flávia Almeida Ribeiro Scalioni; Gabriela El-Corab Fiche; Stefânia Werneck Procópio; Camila Faria Carrada; Raphaella Barcellos Fernandes; Marcio José da Silva Campos; Fernanda Campos Machado (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess dentists' knowledge from Minas Gerais, Brazil, about dentoalveolar trauma (DT) and their experiences during the COVID-19 pandemic. Material and Methods: An online questionnaire with 34 questions was applied to collect personal data, professional training, self-assessment of experience/knowledge about DT, experience in care provided during the social distancing, and knowledge/conduct. The specific responses were evaluated based on the guidelines of the International Association of Dental Traumatology (IADT). Descriptive analysis and Pearson's chi-square test were performed. The level of significance was set at p≤0.05. Results: Most professionals (97.7%) had received information on DT, and only 4.6% of the participants considered their knowledge poor or very poor. However, 92.7% felt the need for more information on the subject. Regarding experiences during the pandemic, 55.7% provided trauma care during that period. Forty percent of the consultations were performed in person, and 33.3% of the professionals noted an increase in cases during the pandemic; 56.6% reported that the frequency did not change. The overall mean number of correct answers about DT was 5.29±2.11, indicating an acceptable level of knowledge. The mean percentage of hits for the specific questions was 44.1%. Conclusion: Although the level of knowledge of the dentists evaluated was acceptable, some aspects were deficient, with the need for more information about the IADT guidelines.